Perancangan Cergam Pesta Paskah Sebagai Media Interaktif Untuk Anak Sekolah Minggu - Alhadid Lutfi Ashari; Sarjono Sarjono; Rahmat Kurniawan (LPPM STIKI Malang, 2023)
In the celebration of Easter there are also activities for children, where children engage in prayer, drama, Easter eggs, and listen to light sermons. Usually, though, when giving a talk to children, children often feel bored, and it is not uncommon for them to play on their own. Hence the introduction of this multifaceted storybook was used as a supporting media for the talk, where children not only listen and see but also interact directly with the activities in the storybook. The method used in this design is DRS. Sadjiman ebbe at Santoyo, Data collection techniques of interviews and observations. With analysis results using a 5w + 1h analysis as a data analysis. The result of this plan of the Passover storybook book has a major media supporting an a4 book with a total of 34 pages using a hardcover, printed on 260 full-color art paper, and has 5 activities in 1 book